Hemophagocytic lymphohistiocytosis/cytokine release syndrome secondary to neoadjuvant pembrolizumab for triple-negative breast cancer: a case study - Patton, Laura; Monteith, Bethany; Heffernan, Paul; Herzinger, Thomas; Wilson, Brooke E. (Frontiers in Oncology, 2024)
As indicaJons for immune checkpoint inhibitors (ICI) for breast cancer conJnue to expand, rare toxiciJes will emerge that require careful consideraJon and mulJdisciplinary management. We report the case of a 40 year old female receiving neoadjuvant pembrolizumab and chemotherapy for locally advanced triple negaJve breast cancer who developed Cytokine Release Syndrome (CRS)/HemophagocyJc LymphohisJocytosis (HLH). CRS/HLH secondary to pembrolizumab are scarcely documented in the literature, and to our knowledge have never been reported in the context of neoadjuvant treatment for breast cancer.